The Role of the Entry of Islamic Influence in 1500-1989 in Gorontalo as a Source of Learning of Local History - Ferrari Yuliawati S; Akhmad Arif Musadad; Musa Pelu (Budapest International Research and Critics University, 2022)
Historical learning is an effort that can be said to be the right way to provide a learning that provides local studies by taking a problem that is close to students and the community, one of which is the entry of Islam in Gorontalo. Where the people of Gorontalo are the majority of adherents of Islam. Islam is one of the few religions that is growing rapidly in Indonesia. Before islam developed very rapidly, indeed Gorontalo was a adherent of the royal system. So that in 1500 there was an Islamic Sultan bringing a good role for the people of Gorontalo, namely spreading the religion of Islam. When historically interesting, the development of Islam in Gorontalo carries the role of an aulia and leaves some stories that are sometimes difficult to understand in logical. But from some literature studies and interview results are indeed the case. From the results of observations, there is a lot of ignorance about how events, impacts and values are obtained. Obviously, this local history learning that utilizes the events of the entry of Islam in Gorontalo is needed to train the critical thinking power of students. Because of the many ignorance of students in the history of their own area. There are many things and relics that can be used as a supporting learning resource, especially in 11th grade high school students related to the entry of Islam in the archipelago. The method used by literature studies where this method uses techniques by conducting a study of books and literature, reports, notes and other literary works that are related to the object being studied. The results of research in historical learning are very relevant to past and present periods so that with this learning source, students get a value that can be a story.